Pathological lesions and global DNA methylation in rat prostate under streptozotocin-induced diabetes and melatonin supplementation - Gobbo, Marina Guimarães [UNESP]; Tamarindo, Guilherme Henrique [UNESP]; Ribeiro, Daniele Lisboa; de Campos, Silvana Gisele Pegorin [UNESP]; Taboga, Sebastião Roberto [UNESP]; Góes, Rejane Maira [UNESP] (Wiley, 2018)
Chronic hyperglycemia increases production of reactive oxygen species, which favors carcinogenesis. The association between diabetes and prostate cancer is controversial. Melatonin has antioxidant, anti-inflammatory, and antiproliferative properties. We investigated whether low doses of melatonin prevent the tissue alterations caused by diabetes and alter prostate histology of healthy rats. We also investigated whether experimental diabetes promoted the development of pathological lesions in the ventral prostate of rats. Melatonin was provided in drinking water (10 μg/kg/day) from age 5 weeks until the end of experiment. Diabetes was induced at 13 weeks by administration of streptozotocin (40 mg/kg, ip). Rats were euthanized at 14 or 21 weeks. Histological and stereological analyses were carried out and the incidence and density of malignant and pre-malignant lesions were assessed. Immunohistochemical assays of α-actin, cell proliferation (PCNA), Bcl-2, glutathione S-transferase (GSTPI), and DNA methylation (5-methylcytidine) were performed. Melatonin did not elicit conspicuous changes in the prostate of healthy animals; in diabetic animals there was a higher incidence of atrophy (93%), microinvasive carcinoma (10%), proliferative inflammatory atrophy, PIA (13%), prostatitis (26%), and prostate intraepithelial neoplasia, PIN (20%) associated with an increase of 40% in global DNA methylation. Melatonin attenuated epithelial and smooth muscle cell (smc) atrophy, especially at short-term diabetes—and normalized incidence of PIN (11%), inflammatory cells infiltrates, prostatitis (0%) and PIA (0%) at long-term diabetes. MLT was effective in preventing inflammatory disorders and PIN under diabetic condition. Although MLT has antioxidant action, it did not influence DNA methylation and not avoid carcinogenesis at low doses.
Keywords: diabetes; melatonin; prostate; prostate cancer; rat